Alternative projections : experimental film in Los Angeles 1945-1980 - James, David E., 1945-; Hyman, Adam (John Libbey Publishing, 2015)
Alternative Projections: Experimental Film in Los Angeles, 1945-1980 is a groundbreaking anthology that features papers from a conference and series of film screenings on postwar avant-garde filmmaking in Los Angeles sponsored by Filmforum, the Getty Foundation, and the University of Southern California's School of Cinematic Arts, together with newly-commissioned essays, an account of the screening series, reprints of historical documents by and about experimental filmmakers in the region, and other rare photographs and ephemera. The resulting diverse and multi-voiced collection is of great importance, not simply for its relevance to Los Angeles, but also for its general discoveries and projections about alternative cinemas.